2022
DOI: 10.1039/d1ay02219a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of the influence of silver cluster ions on the MALDI-TOF-MS analysis of polystyrene nanoplastic polymers

Abstract: Polystyrene nanoplastic mass spectra suffered interference from silver cluster ions. Nonpolar matrices enhanced the polystyrene nanoplastic mass spectral quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This finding could present an advantage for the analysis of synthetic polymers with MALDI since the addition of a cationizing agent will not be required for polymers with sufficiently high absorption at the wavelength of the second laser. In addition, prior studies reported that silver salts when used with very acidic matrices can produce spectral interferences in the analysis of low-molecular-weight polymers. , Hence, MALDI-2 could be very beneficial for this kind of study of PS without spectral interferences. Lastly, other UV-absorbing polymers, such as those containing aromatic systems, could benefit from a MALDI-2-based analytical approach.…”
Section: Resultsmentioning
confidence: 99%
“…This finding could present an advantage for the analysis of synthetic polymers with MALDI since the addition of a cationizing agent will not be required for polymers with sufficiently high absorption at the wavelength of the second laser. In addition, prior studies reported that silver salts when used with very acidic matrices can produce spectral interferences in the analysis of low-molecular-weight polymers. , Hence, MALDI-2 could be very beneficial for this kind of study of PS without spectral interferences. Lastly, other UV-absorbing polymers, such as those containing aromatic systems, could benefit from a MALDI-2-based analytical approach.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, a variety of cations have been widely used for the analysis of different types of polymers and the formation of [M + cation] n+ adducts (Na + , Ag + , K + , Cu 2+ , Cs + , Cr 3+ ) have been observed, while the anions applied to induce the so ionization of these particular polymers, the [M + anion] nÀ adducts (anion ¼ NO 3 À , Cl À , I À , SO 4 2À and Br À ) have been formed. 115,[122][123][124][125][126] Furthermore, metal salts are available at low cost and could easily be found in chemistry laboratories, making them useful for assisting the ionization system, which, would be a much more practical and economical choice. [60][61][62] Metal salts-based developed strategies would provide a promising platform for MS techniques in polymer characterization.…”
Section: Development Of a Metal Saltassisted Ionization System For Msmentioning
confidence: 99%
“…For some special cases of polymers, polar matrices could also be used. 123,125,126 6.2. Prospective for future…”
Section: Challengesmentioning
confidence: 99%
“…Indole is an electron-rich compound widely distributed in biological systems such as proteins (amino acid tryptophan side chain) and alkaloids . Some existing indole-related MALDI matrices are trans-3-indoleacrylic acid (IAA) for polymers and steroids; indole-3-pyruvic acid (IPA) for peptides and proteins; and 9H-pyrido­[3,4- b ]-indole (nor-harmane) for lipids, proteins, peptides, carbohydrates, and synthetic polymers. , Nitro-containing matrices generally have a nitro group attached to a benzene ring, such as 9-nitroanthracene (9-NA) for polymers and organic ligands, , 2-nitrophloroglucinol (2-NPG) for protein multiple charging, 5-nitrosalicylic acid (5-NSA) for glycan in source decay (ISD), 3-hydroxy-4-nitrobenzoic acid (3H4NBA)/3-hydroxy-2-nitrobenzoic acid (3H2NBA) for peptide ISD, , and 4-nitroaniline (PNA) for lipids . Nitro substituted β-carboline (nor-harmane) and carbazole derivatives were also reported. , …”
Section: Introductionmentioning
confidence: 99%